Incorporating Arbitration Clauses: The Sacrifice of Consistency at the Altar of Experience - Allison, Simon; Dharmananda SC, Kanaga (Kluwer Law International, 2014)
This article considers the varying judicial approaches to the question of incorporation of arbitration agreements by reference to another contract, schedule of terms, or trading rules. In particular, attention is directed to the approach taken by English courts in considering whether a subsequent holder of a bill of lading is bound by an arbitration agreement contained in a charterparty. In that context, English courts required an express reference in a bill of lading to the charterparty arbitration clause before it could be regarded as part of the contract. General words purporting to incorporate the terms and conditions of a charterparty would not be sufficient. This article examines the development of this strict approach to incorporation in the maritime context, its application to contractual disputes outside that context and recent case law signalling a more flexible approach to the question based on the intention of the parties involved.